Comparison of the results of early, delayed and elective surgery in biliary pancreatitis - Abdülkadir BEDİRLİ; Erdoğan M. SÖZÜER; Ömer ŞAKRAK; Hülya BABAYİĞİT; Zeki YILMAZ (Turkish Journal of Gastroenterology, 2019)
-